Farmers’ performance and subject pool effect in decentralized bargaining markets - Waichman, Israel; Ness, Christiane (Economics letters, 2012)
We report results from a decentralized bargaining market experiment conducted with farmers and students. Our results indicate that despite its bad reputation, performance is highly efficient (although not as efficient as the competitive equilibrium prediction). Farmers and students perform similarly regarding quantities, prices, and allocative efficiencies, but not regarding payoff allocations between buyers and sellers. ► We conducted a decentralized bargaining experiment with both farmers and students. ► We find that performance is highly efficient. ► Nevertheless, it is not as efficient as theory predicts. ► We do not find differences in aggregate performance between farmers and students. ► But farmers assign higher payoffs to buyers than students.